2006
DOI: 10.1128/jcm.01433-06
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Complex and Mycobacterial Heat Shock Proteins in Lymph Node Tissue from Patients with Pulmonary Sarcoidosis

Abstract: We demonstrated that not whole Mycobacterium tuberculosis but its particular antigens, hsp70 Mtb , hsp65 Mtb , and hsp16 Mtb , are present in lymph node tissues of patients with sarcoidosis (SA). hsp16 Mtb occurs in the early stage of SA, whereas hsp70 Mtb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
0
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 12 publications
4
58
0
10
Order By: Relevance
“…This antigen increases expression of costimulatory molecules, suggesting that MTB-hsp70 positivity could lead to a break in immune tolerance and subsequent autoimmune disease (89). Consistent with these positive serology observations, mycobacterial hsp16, hsp65, and hsp70 have been detected in sarcoidal tissue by immunostaining (77).…”
Section: Immunologic and Antigen Isolationsupporting
confidence: 68%
See 1 more Smart Citation
“…This antigen increases expression of costimulatory molecules, suggesting that MTB-hsp70 positivity could lead to a break in immune tolerance and subsequent autoimmune disease (89). Consistent with these positive serology observations, mycobacterial hsp16, hsp65, and hsp70 have been detected in sarcoidal tissue by immunostaining (77).…”
Section: Immunologic and Antigen Isolationsupporting
confidence: 68%
“…Drake and coworkers found MTB rRNA in 48%, MTB rpoB (RNA polymerase) DNA in 24%, and the MTB-specific insertion sequence IS6110 in 0% of 25 patients with sarcoidosis, but none of these sequences was found in 25 control subjects (76). Other authors have also reported low levels or the absence of the MTB IS6110 sequence in sarcoidosis samples (77,78). Whether this finding reflects the differential sensitivity of these tests or the presence of a MTB-related organism that lacks IS6110 is unknown.…”
Section: Nucleic Acid Identificationmentioning
confidence: 94%
“…Song and colleagues (3) used matrix-assisted laser desorption/ionization time of flight mass spectrometry to demonstrate the presence of mycobacterial catalase-peroxidase (katG) proteins in sarcoidosis granulomas. Mycobacterial heat-shock proteins were also evident in Polish sarcoidosis granulomas (4). Major histocompatibility complex (MHC) Class II alleles are associated with protection or susceptibility in patients with sarcoidosis (5,6).…”
mentioning
confidence: 97%
“…Previous studies have reported humoral responses to mycobacterial antigens among sarcoidosis subjects (4,15) as well as the detection of mycobacterial nucleic acids and proteins in sarcoidosis granulomas (3,5,15). We performed enzyme-linked immunospot (ELISPOT) assays to assess for cellular recognition of two Mycobacterium sp.…”
mentioning
confidence: 99%